Cyclic resistance change in perpendicularly magnetized Co/Ni nanowire induced by alternating current pulse injection - Kwon, J. (2017)
We report on cyclic anisotropic magnetoresistance change induced by current pulse injection in perpendicularly magnetized Co/Ni nanowire. By alternating the polarity of the injection pulse, domain walls (DWs) can be deterministically created and annihilated within the nanowire. The injection induces a combined effect of spin transfer torque and Oersted field that leads to simultaneous creation and driving of DWs in the nanowire. DW created by single pulse injection exhibits a fixed depinning field. For multi-pulse injection, the depinning field increases and this is ascribed to the formation of DWs with opposite chirality.